Architecture and network-on-chip implementation of a new hierarchical interconnection network - Awal, Md Rabiul (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2015)
Interconnection network is an important issue for massively parallel computer due to the increasing capability and smaller size of the processing elements. In this thesis, we propose a new hierarchical interconnection network called Midimew-connected Mesh Network (MMN) for massively parallel computer. The proposed network consists of multiple basic modules which are 2-D mesh (2m×2m) network and are hierarchically interconnected by a 2-D midimew (2m×2m) network to build the higher levels. Hence, we call it Midimew-connected Mesh Network (MMN). Architectural details, address-ing of nodes, and routing of message of MMN are discussed in details. We have ex-plored various aspects such as network degree, diameter, cost, average distance, bisec-tion width, wiring complexity of the MMN and compared them with other networks. It is shown that the MMN possesses several attractive features, including constant de-gree, small diameter, low cost, small average distance, moderate bisection width, and high fault tolerant performance than that of other conventional and hierarchical inter-connection networks. Network-on-Chip (NoC) addresses the implementability of in-terconnection network on a single chip. We have examined the NoC implementation of MMN. The result shows that, a Level-3 MMN can be laid on a VLSI surface with 4 layers only. We have considered no jump crossing links method to determine the number of layers of MMN.